Decreased Vitamin C Intake from Food and Supplements in the US Pregnant and Non-Pregnant Population: From NHANES 1999–2018. (14th June 2022) - Miketinas, Derek; Luo, Hanqi; Firth, Josh; Bender, Tonya; Bailey, Ariana; McMilin, Colleen; Brinnk, Lauren
Abstract: Objectives: To examine how vitamin C intake among women of reproductive age changed from 1999 to 2018 using data from 10 cycles of the National Health and Nutrition Examination Survey (NHANES) from 1999–2000 to 2017–2018. Methods: Usual vitamin C intake and prevalence of inadequate intake were estimated among pregnant and non-pregnant women 20–44 y who participated in NHANES 1999–2018 (n = 11, 129), using the National Cancer Institute Method. Covariates included dietary recall sequence, intake day of the week, and dietary supplement use. Regression models were used to test for trends in vitamin c intake from foods, supplements, foods and supplements combined, and prevalence of inadequate vitamin C intake over 10 cycles of NHANES. Results: 1, 392 were pregnant at the time of the exam. Vitamin C intake from foods alone in pregnant women decreased from 125 ± 6.7 mg in 1999–2000 to 103 ± 5.3 mg in 2017–2018 (p for trend = .0003). Supplemental vitamin c intake among pregnant women decreased from 140 ± 2.8 mg in 1999–2000 to 56 ± 0.9 mg in 2009–2010, followed by an apparent plateau between 2011–2018 (p for trend = .02). Consequently, intake foods and supplements combined decreased from 265 ± 31.9 mg in 1999–2000 to 158 ± 16.7 mg in 2017–2018 (p for trend = .0001). Inadequate intake (% < EAR) increased from 10.5 ± 2.2% in 2001–2002 to 17.2 ± 3.1% in 2017–2018 (p for trend = .015). Vitamin C intake from foods alone in non-pregnant women (n = 9, 737) decreased from 84 ± 3.9 mg in 1999–2000 to 71 ± 2.5 mg in 2017–2018 (p for trend < .0001). Supplemental vitamin C intake among non-pregnant women decreased from 101 ± 1.3 mg in 1999–2000 to 41 ± 0.5 mg in 2009–2010 followed by an increase to 86 ± 2.7 mg in 2017–2018 (p for trend = .0075). Consequently, intake from foods and supplements combined decreased from 186 ± 15.4 mg in 1999–2000 to 119 ± 5.9 mg in 2009–2010 followed by an increase to 157 ± 28.4 mg in 2017–2018 (p for trend = .0045). Inadequate intake increased from 27.5 ± 2.5% in 1999–2000 to 38.6 ± 2.4% in 2017–2018 (p for trend < .0001). Conclusions: Over the past 2 decades, decreases in vitamin C intake from foods has outpaced the more recent increases in supplemental vitamin C intake among women 20–44 y. Pregnant women's vitamin C intake from both foods and supplements decreased during this time, which may result in an increased risk of infections, premature birth, and eclampsia. Funding Sources: Funded by the Reckitt|Mead Johnson Nutrition.